Sintesis Oktil Sinamat dengan Metode Sonokimia dan Potensinya sebagai Antikolesterol - Verdia Mutiara, Erlita; Wildan, Achmad; Dian Advistasari, Yustisia; Indriyanti, Erwin (Jurnal Farmasi (Journal of Pharmacy), 2022)
Cinnamic acid derivatives play a very important role in the synthesis of other important compounds and as precursors for the synthesis of cinnamic esters. Cinnamate esters have diverse bioactivity. This group has antioxidant, hepatoprotective, anti-inflammatory, anxiolytic, insect repellent, antidiabetic and anticholesterol activities. Octyl cinnamate is a cinnamic acid derivative which is thought to be efficacious as a cholesterol lowering agent. Cholesterol has been known as the main cause of the process of atherosclerosis, namely the process of calcification and hardening of the arteries. As a result of this process the blood vessels, especially coronary arteries become narrow and block blood flow. Octylcinnamate has been successfully synthesized from the esterification reaction between cinnamic acid and n-octanol with a concentrated sulfuric acid catalyst. The sonochemical method is one of the methods developed in this synthesis process because it is very easy to do, efficient, with high yields, short time and environmentally friendly. From the results of the synthesis, identification of compounds was carried out through melting point and FTIR spectrophotometry. Based on the interpretation of data from FTIR that the synthesis product was n-octyl cinnamate. The synthesis was carried out at 600C with a sonication time of 7 hours. The anticholesterol activity of the optimally synthesized n-octyl cinnamate compound at a concentration of 5 ppm was 55.42%.